The Burden of Indigenous People in Dealing with State Regulation - M. Syamsudin (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The most common type of conflict involving indigenous people is the dispute on the ownership of economic resources and cultural sites which are convicted and guaranteed as traditional indigenous rights. In this regard, indigenous people stand vis a vis with investors’ interest which is usually safeguarded by state legal instruments. Indigenous people are shaky in this kind of conflict and in the factual cases, the process to weaken and destroy indigenous community has been made through regulations, policies, as well as real actions made by the government. Keywords: Burden of Indigenous People, the Ideology of Legal Centralism, State Regulation